The Influence of Intellectual Capital to Financial Performance at Real Estate and Property in Jakarta Stock Exchange (JSE) - Nasih, Moh.; Iswati, Sri (Universitas Brawijaya, Indonesia, 2011)
To overcome the competition, a company not only focuses on physical capital, but also focuses on intellectual capital. Company can achieve a competitive advantage and earn profit by owing intellectual capital Intellectual capital rests on a potential link between intellectual capital on one hand and corporate performance on the other hand. A company will grow up if a growing number of physical capitals in the same line with a growing number of intellectual capitals. The purpose of this empirical study is to investigate the influence of intellectual on real estate and property performance, especially financial performance. This study uses empirical data from Indonesia Capital Market Directory 2005 that issued of Jakarta Stock Exchange (JSE). This research use quantitative analysis. The population of the research is real estate and property ar listed in JSE. The hypothesis test conducted by regression analysis model with the degree of significant at 0.05. The main conclusion from this particular study is intellectual capital has influence on real estate and properly performance.